THE UNIVERSITY EDUCATION: BETWEEN THE HISTORICAL MISSION AND REAL PROSPECT - Sauch, P. (Continuing Professional Education: Theory and Practice, 2019)
In the article, basing on the analysis of new tendencies of unification, commercialization and mass outspread in university education an algorithm of utilitarian pragmatics in professional training with “pragmatics” of fundamental knowledge and nationalcultural traditions synthesis is suggested which will allow a modern university not only to maintain itself, but to continue performing an important social and cultural mission. The university of the XXI century should prepare the new generations of the professionals and harmonically cultured people that will be able to be responsible for their actions. The global processes, on the one hand, form the tasks to teach people how to coexist harmonically basing on the historical and cultural knowledge, the ways of other nations‘ thinking; on the other hand, they focus on the keeping of the cultural unique identity, languages and national systems of education.